Nordic interior design - Roth, Manuela. 4 0 16; 5 (Salenstein, Switzerland : Braun Publishing, 2011)
Profiles the interior design of homes and commercial spaces in Scandinavia.
Includes index.
Text in English and German.
Keywords: 2 -- 0; 6; Decoration;Decoration. -- Interior decoration;Commercial buildings;Commercial buildings -- Scandinavia.;Scandinavia.; 20; 2